RETRACTED: The Integration of the Neurosciences, Child Public Health, and Education Practice: Hemisphere-Specific Remediation Strategies as a Discipline Partnered Rehabilitation Tool in ADD/ADHD - Leisman, Gerry; Mualem, Raed Z.; Machado, Calixto (Frontiers in Public Health, 2013)
ADHD is the most common and most studied neurodevelopmental problem. Recent statistics from the CDC state that 11% approximately 1 out of every 9 children in the US and 1 in 5 high school boys are diagnosed with ADHD. Lacking from treatment is an interdisciplinary knowledge-based strategy to intervention with child public health concerns addressed the educational system. This study is based on previous findings that ADHD children possess underactivity between sub-cortical and cortical regions. An imbalance of activity or arousal in one area can result in functional disconnections similar to that seen in split-brain patients. As ADD/ADHD children exhibit deficient performance on tests measuring perceptual laterality, evidence of weak laterality or failure to develop laterality has been found across various modalities (auditory, visual, tactile) resulting in abnormal cerebral organization and associated dysfunctional specialization needed for lateralized processing of language and non-language function. This pilot study examines groups of ADD/ADHD and control elementary school children all of whom were administered all the subtests of the Wechsler Individual Achievement Tests, the Brown Parent Questionnaire, and given objective performance measures on tests of motor and sensory coordinative abilities. Results measured after a 12-week remediation program aimed at increasing the activity of the hypothesized underactive right hemisphere function, yielded significant improvement of greater than two years in grade level in all domains except in mathematical reasoning. The treated group also displayed a significant improvement in behavior with a reduction in Brown scale behavioral scores. Non-treated control participants did not exhibit significant differences during the same 12-week period in academic measurements, but did so when compared to the treated group. Results are discussed in the context of the concept of functional disconnectivity in ADD/ADHD children.